Improvements in Biosolids Quality Resulting from the Clean Water Act. (1st February 2014) - Hundal, Lakhwinder S.; Kumar, Kuldip; Cox, Albert; Zhang, Heng; Granato, Thomas
ABSTRACT: : Promulgation of the Clean Water Act (CWA) authorized the United States Environmental Protection Agency (U.S. EPA) to regulate quality standards for surface waters and establish regulations limiting the amounts and types of pollutants entering the nation's waters. U.S. EPA imposed national pretreatment standards on industrial wastes discharged to the collection systems of publicly owned treatment works (POTWs) and promulgated General Pretreatment Regulations in 1978. This study analyzed trace metals data from the National Sewage Sludge Surveys conducted by U.S. EPA and the American Metropolitan Sewage Agencies (AMSA) to evaluate the effect of implementation of the national industrial pretreatment standards on concentrations of trace metals in sludges generated by POTWs in the United States. The data showed that implementation of pretreatment programs has been highly effective in reducing the amount of pollutants that enter POTWs and has resulted in a substantial reduction in the levels of trace metals in the municipal sludges. Concentrations of chromium, lead, and nickel in sludge declined by 78, 73, and 63%, respectively, within a year after promulgation of General Pretreatment Regulations. Resulting from these measures, metal concentrations in the sludges generated by a majority of POTWs in the United States are sufficiently low that the sludges can be classified as biosolids and also meet the U.S. EPA's exceptional quality criteria for trace metals in biosolids. This improvement gives POTWs the option to use their biosolids beneficially through land application.